2019
DOI: 10.3390/f10121131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salt on Root Aeration, Nitrification, and Nitrogen Uptake in Mangroves

Abstract: The potential effects of salt on the growth, root anatomy, radial oxygen loss (ROL), and nitrogen (N) dynamics in mangroves were investigated using the seedlings of Avicennia marina (Forsk.) Vierh. The results showed that a moderate salinity (200 mM NaCl) appeared to have little negative effect on the growth of A. marina. However, higher salt stresses (400 and 600 mM NaCl) significantly inhibited the biomass yield. Concentrations of N in the roots and leaves decreased sharply with increasing salinity. Neverthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…Additional evidence indicates that adjacent mudflat sediments usually have higher porewater concentrations of NH 4 + than in mangrove soils, suggesting that the difference is due to tree uptake [11]. These data are circumstantial, but support experimental data showing a strong preference by mangroves for ammonium (and nitrate) for their growth and nutrition [12][13][14][15]. Nitrite and nitrate are often found in mangrove porewater [4,11], but concentrations show very irregular patterns with increasing soil depth.…”
Section: Dissolved N Concentrations In Tidal Waters and Porewatersupporting
confidence: 64%
See 1 more Smart Citation
“…Additional evidence indicates that adjacent mudflat sediments usually have higher porewater concentrations of NH 4 + than in mangrove soils, suggesting that the difference is due to tree uptake [11]. These data are circumstantial, but support experimental data showing a strong preference by mangroves for ammonium (and nitrate) for their growth and nutrition [12][13][14][15]. Nitrite and nitrate are often found in mangrove porewater [4,11], but concentrations show very irregular patterns with increasing soil depth.…”
Section: Dissolved N Concentrations In Tidal Waters and Porewatersupporting
confidence: 64%
“…Abbreviations: DNRA= dissimilatory nitrate reduction to ammonium; anammox = anaerobic ammonium oxidation. Source: [9,15,[55][56][57][58]129,.…”
Section: Forest Soil N Transformationsmentioning
confidence: 99%
“…It has been shown that sea-level rise caused by climate change may affect the growth and distribution of mangroves [72][73][74]. Large-scale planting of mangroves has been applied as a mitigation strategy for mangrove loss [34].…”
Section: Comparison Among Mangrove Forestsmentioning
confidence: 99%